Recent results on heavy flavours and quarkonia from ALICE - Fionda Fiorella (EPJ Web of Conferences)
Heavy-flavour hadrons, containing at least one charm or beauty quark, are excellent probes of the deconfined medium created in ultrarelativistic heavy-ion collisions, known as quark–gluon plasma. Results in smaller collision systems, such as proton–proton and p–Pb collisions, besides representing an important baseline for interpreting heavy-ion measurements, are crucial to test perturbative QCD calculations and hadronisation mechanisms in the absence of hot medium effects, as well as to search for commonalities with heavy-ion systems. Recently, measurements in proton–proton and p–Pb collisions have revealed unforeseen features with respect to the expectations based on previous results from e+e− and ep collisions, showing that fragmentation fractions of heavy quarks are not universal. In this contribution, an overview of the most recent ALICE heavy-flavour measurements, along with the comparison to available calculations, will be discussed.